1987
DOI: 10.1152/jappl.1987.62.5.1786
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary strength and muscle characteristics in untrained men and women and male bodybuilders

Abstract: Eight untrained women (F), 13 untrained men (M), and 11 male bodybuilders (BB) did maximal elbow flexions on an isokinetic dynamometer at velocities of 30, 120, 180, 240, and 300 degrees/s, from which impact torque (IT), peak torque (PT), and work (W) were measured. Biceps and total flexor cross-sectional area (CSA) were measured by computerized tomographic scanning. Muscle fiber area, fiber composition, and collagen volume density were determined from single needle biopsies of biceps brachii. Biceps fiber num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
75
2
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 19 publications
12
75
2
3
Order By: Relevance
“…Other studies have found that in UT subjects (42), middle-distance runners (5), trained cyclists (11), and subjects representing a wide range of physical activity levels (33), females had a higher percentage of type I fibers than males. At all training levels in the present study, the area of all the fiber types was smaller in females than in males, especially for type II fibers, which is in accordance with previous observations (5,35,39,40,42). As a consequence, the calculated fiber composition expressed relative to fiber area revealed that type I fibers accounted for a relatively larger area in females than in males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies have found that in UT subjects (42), middle-distance runners (5), trained cyclists (11), and subjects representing a wide range of physical activity levels (33), females had a higher percentage of type I fibers than males. At all training levels in the present study, the area of all the fiber types was smaller in females than in males, especially for type II fibers, which is in accordance with previous observations (5,35,39,40,42). As a consequence, the calculated fiber composition expressed relative to fiber area revealed that type I fibers accounted for a relatively larger area in females than in males.…”
Section: Discussionsupporting
confidence: 92%
“…However, UT females had a higher percentage of type I fibers than UT males. Previously, a similar fiber type composition in females and males has been found in UT subjects (5,35,39) as well as in physical education students (40). Other studies have found that in UT subjects (42), middle-distance runners (5), trained cyclists (11), and subjects representing a wide range of physical activity levels (33), females had a higher percentage of type I fibers than males.…”
Section: Discussionsupporting
confidence: 62%
“…It cannot be argued that hypertrophy in these older muscles was entirely the result of connective tissue proliferation, because the increase in fiber size was at least equivalent to that of the whole muscle. Furthermore the greatly hypertrophied muscles of bodybuilders show no evidence of connective tissue proliferation (32). In the previously cited study of rat soleus (16), hypertrophy after 30 days of overload was not associated with connective tissue proliferation, an increase in interstitial fluid volume, or a decrease in protein content.…”
Section: Discussionmentioning
confidence: 74%
“…7 -9 The strength athletes exhibit extreme muscle hypertrophy, 14,15 with performance measured either as physical appearance or single-repetition maximal force production (strength), rather than the multiple contraction events typical of sprint-related athletes. 7 -10 Because the a-actinin protein is important for maintaining the myofibrillar array within represent another mechanism explaining our findings.…”
Section: Discussionmentioning
confidence: 99%